SOD2 genetics regulating mitochondrial management of oxidative stress is tied to chemical sensitivity in Gulf war veterans - Beatrice Alexandra Golomb; Leeann Bui; Brinton Keith Berg (Scientific Reports)
Abstract Multiple chemical sensitivity (MCS), though viewed by many as psychogenic, was presumptively tied to genetic variation in superoxide dismutase 2 (SOD2), involved in conversion of mitochondrial superoxide to hydrogen peroxide, in Japanese paper pulp workers. Gulf War veterans (GWV) have increased MCS compared to nondeployed persons. In data from GWV and nonveterans, we assessed whether altered oxidative stress management via SOD2 polymorphism was tied to self-rated chemical sensitivity. Sixty white predominantly male GWV and age-similar nonveterans completed self-ratings of chemical sensitivity, and underwent both nuclear DNA analysis for SOD2 variants and mitochondrial haplogroup assessment. SOD2 Ala16 (vs. Val16) significantly predicted self-rated chemical sensitivity in GWV and in the total sample (ordinal logistic regression with robust SEs): OR(SE)[95% CI] = 3.56(1.83)[1.30, 9.74], p = 0.013 (total sample); OR[95% CI](SE) = 6.36(4.85)[1.42, 28.4], p = 0.015 (Gulf-deployed). Significance was sustained with adjustment for mitochondrial haplogroup U (not itself significant) and when reappraised with nonparametric trend tests (Kendall’s Tau, Spearman Ranked Correlation Coefficient). The findings extend evidence of SOD2 polymorphism ramifications for chemical sensitivity to a new chemically exposed sample, implicating mitochondrial oxidative stress management as a (though not necessarily the exclusive) key factor in chemical sensitivity. Findings comport with burgeoning evidence inculpating mitochondrial impairment and oxidative stress in many drug/chemical/environmental factors’ toxicity irrespective of the agent’s nominal mechanism of action. This supports chemical sensitivity as a physiological, not a psychogenic condition.